2012
DOI: 10.1152/ajplung.00251.2011
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q1as a probe for mitochondrial complex I activity in the intact perfused hyperoxia-exposed wild-type andNqo1-null mouse lung

Abstract: Bongard RD, Myers CR, Lindemer BJ, Baumgardt S, Gonzalez FJ, Merker MP. Coenzyme Q 1 as a probe for mitochondrial complex I activity in the intact perfused hyperoxia-exposed wild-type and Nqo1-null mouse lung. Am J Physiol Lung Cell Mol Physiol 302: L949-L958, 2012. First published January 20, 2012 doi:10.1152/ajplung.00251.2011.-Previous studies showed that coenzyme Q 1 (CoQ1) reduction on passage through the rat pulmonary circulation was catalyzed by NAD(P)H: quinone oxidoreductase 1 (NQO1) and mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…Multiple endogenous and exogenous oxidants activate NADPH, and many have been used to induce cellular injury in animal and in vitro models. Examples include hyperoxia, hypoxia, inhaled particles, xanthine oxidase, cigarette smoke, and other ROS themselves, all of which contribute to mitochondrial dysfunction by overwhelming enzymes within the OXPHOS metabolic pathway (9,18,69,158). For example, Ghouleh et al (57) recently demonstrated increased expression of Nox-1 in the pulmonary endothelium of patients with PH.…”
Section: Metabolic Pathways and Mitochondria In Pulmonary Hypertension-the "Metabolic Theory"mentioning
confidence: 99%
“…Multiple endogenous and exogenous oxidants activate NADPH, and many have been used to induce cellular injury in animal and in vitro models. Examples include hyperoxia, hypoxia, inhaled particles, xanthine oxidase, cigarette smoke, and other ROS themselves, all of which contribute to mitochondrial dysfunction by overwhelming enzymes within the OXPHOS metabolic pathway (9,18,69,158). For example, Ghouleh et al (57) recently demonstrated increased expression of Nox-1 in the pulmonary endothelium of patients with PH.…”
Section: Metabolic Pathways and Mitochondria In Pulmonary Hypertension-the "Metabolic Theory"mentioning
confidence: 99%
“…The NQO1 in the lung has been investigated in several studies ( 11 , 15 , 16 ). Recently, Bongard et al have shown that alterations in CoQ1 redox metabolism, either by addition of the complex I inhibitor rotenone or exposure of the animal to hyperoxia, can reveal a decrease in mitochondrial complex I activity ( 18 ). In addition, by using bovine pulmonary arterial EC, they have demonstrated that the cytoplasmic redox status, as reflected in the NADH/NAD + and NADPH/NADP + ratios, affects t-PMET reduction of thiazine compounds and NQO1-mediated quinone reduction ( 16 ).…”
Section: Redox Buffer Systemsmentioning
confidence: 99%